2011
DOI: 10.1210/jc.2010-2216
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Sex Hormones and Sexual Function in Middle-Aged and Older European Men

Abstract: These findings suggest that different hormonal mechanisms may regulate sexual functioning (T) vs. the psychological aspects (E2) of male sexual behavior. Moreover, there was a T threshold for overall sexual function such that at levels greater than 8 nmol/liter the relationship between T and sexual function did not become stronger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 50 publications
5
59
0
Order By: Relevance
“…Hypoandrogenism in men is manifested, among other things, by a lack of interest in sex (no sexual fantasies), lack of spontaneous, morning erections, ED during sexual stimulation and difficulty in achieving orgasm [12,13]. EMAS revealed that among men above 40, those with the lowest levels of total and free testosterone reported significantly lower sexual function compared to men with the highest testosterone levels [14]. Androgen deficiency in older men creates a clinical syndrome called late onset hypogonadism (LOH), which is associated with multiple end-organ deficits [15].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoandrogenism in men is manifested, among other things, by a lack of interest in sex (no sexual fantasies), lack of spontaneous, morning erections, ED during sexual stimulation and difficulty in achieving orgasm [12,13]. EMAS revealed that among men above 40, those with the lowest levels of total and free testosterone reported significantly lower sexual function compared to men with the highest testosterone levels [14]. Androgen deficiency in older men creates a clinical syndrome called late onset hypogonadism (LOH), which is associated with multiple end-organ deficits [15].…”
Section: Introductionmentioning
confidence: 99%
“…E 2 was the only hormone associated with sexual function-related distress, such that higher levels were related to greater distress. 20 Although several interesting studies have elucidated the role of E 2 in male reproduction, data on the peripheral levels of sex steroids are lacking. Huhtaniemi et al 21 reported that increased oestrogen activity rather than decreased androgen activity is associated with longer androgen receptor CAG repeats.…”
Section: Discussionmentioning
confidence: 99%
“…Cronbach's alpha coefficient has also indicated a high internal consistency. 12,13 Scoring the IIEF domain of erectile function allowed the classification of each patient as having no (26)(27)(28)(29)(30), mild (17)(18)(19)(20)(21)(22)(23)(24)(25), moderate (11)(12)(13)(14)(15)(16) or severe (0-10) ED. At the same visits during which they were assessed for ED, all patients were also interviewed to gather their sociodemographic characteristics and relevant medical history.…”
Section: Ed Assessmentmentioning
confidence: 99%
“…In particular, total serum T concentrations lower than or equal to 230 ng/ dL (8 nmol/L) have been associated with worse sexual functioning and higher rates of erectile dysfunction. 92 …”
Section: Consequences Of Hormonal Changes Related To Male Agingmentioning
confidence: 99%
“…47 In particular, in the EMAS study lower serum free T levels have been more strongly associated with severe sexual dysfunction (such as increased erectile dysfunction and lower masturbation frequency). 83,92 Less data are available on sexual function in the BLSA and MrOS studies 97 (Table 3). Overweight and obesity are strongly associated to the decline of both total serum T and SHBG in several studies such as the MMAS, 37 and diabetes 107 (Table 3).…”
Section: Main Outcomes Of Cohort Studiesmentioning
confidence: 99%